Rapid Determination of Gross Alpha/Beta Activity in Water Based on Reverse Osmosis Membrane Enrichment Pretreatment - Ruiqi Zhang; Jianye Wang; Nanjing Zhao; Xuyun Huang (Science and Technology of Nuclear Installations)
Radioactivity of gross alpha/beta is an index of water quality detection, which can reflect the radioactivity intensity of water. However, the traditional detection method of these parameters, thick source method, has problems of cumbersome and time consumption in sample preparation and cannot realize the rapid detection on-site. Based on this, this paper studies the enrichment method based on reverse osmosis membrane to accurately and quickly determine the gross α and gross β in water by using the reverse osmosis membrane as the carrier and enriching the radionuclides in water to the high-pressure side of the reverse osmosis membrane to replace the sample preparation process in traditional thick source method, so as to shorten the sample processing time in the detection process and avoid the cumbersome sample preparation process. The reverse osmosis membrane enrichment method for the determination of gross in 241Am and 40KCl standard solutions was used to study gross alpha/beta radioactivity, and the results showed that the average recoveries of radioactivity of gross alpha/beta were 95.0% and 93.6%, respectively. At the same time, the results of the thick source method and the reverse osmosis membrane method on the gross alpha/beta of actual water samples in 5 different regions were compared. It showed that the thick source method and the reverse osmosis membrane method had a good consistency in the detection results of total α and total β radioactivity, and the reverse osmosis membrane method had better stability than the thick source method. The average relative standard deviations (RSD) of the gross alpha and gross beta activity obtained by the thick source method are 11.9% and 7.3%, respectively, while RSD of the gross alpha and gross beta radioactivity obtained by the reverse osmosis membrane method were 6.9% and 4.7%, respectively. The preparation time of single sample was reduced by 75.7%, and the overall detection cycle time was reduced by 68.1%.